PENGARUH PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) TERHADAP KEMAMPUAN PENALARAN MATEMATIS SISWA MTs - Linuhung, Nego; Sudarman, Satrio Wicaksono (UNIVERSITAS MUHAMMADIYAH METRO, 2016)
The research was conducted to find out the influence of Group Investigation (GI) of Cooperative Learning methods toward the studentâs ability of mathematical reasoning. The research design was quasi-experimental the nonequivalent posttest-only control group design consisting of one experimental class (Group Investigation of Cooperative Learning) and one control class. The research population was all the second-semester students of VIII grade of MTs Negeri 1 Lampung Timur in the academic year of 2015/2016. The research instruments used were mathematical reasoning ability test. Data Analyze mathematical reasoning ability was used independent sample t-test. The results showed that: (1) mathematical reasoning ability using Group Investigation of Cooperative Learning was higher than conventional learning.Keywords: Mathematical Reasoning Ability, Group Investigation (GI) of Cooperative Learning